Investigating the Antihyperglycaemic Effect of Vetiveria zizanioides (L.) Nash Root Extract in Alloxan-induced Diabetic Rats - Sanjay Kumar Karan; Dilipkumar Pal; Sagar Kumar Mishra; Arijit Mondal (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
Vetiveria zizanioides (L.) Nash (family: Poaceae) is commonly known as ’Khas-Khas’ in Bangladesh and India. The aim of this study is to evaluate the antihyperglycaemic activity of the ethanol extract of roots of Vetiveria zizanioides (L.) Nash, in alloxan-induced diabetic rats. Wistar albino rats weighing 250- 350 g of both sexes were selected for the present investigation Antihyperglycaemic Effect of Vetiveria zizanioides (L.) Nash Root Extract. Alloxan monohydrate (150 mg/kg) was administered to Wister albino rats via the interperitoneal route. The diabetic rats were then placed into 6 groups, following the stabilization of hyperglycaemia. The first group was untreated; the second group received a reference standard, glibenclamide (10 mg/kg) and the next four groups received ethanol extract of V. zizanioides roots at the doses of 100, 250, 500 and 750 mg/kg, respectively each day. Treatment was provided via the oral route for 28 days and fasting sugar level was monitored over this period. Acute toxicity (oral and interperitoneal) studies as well as phytochemical screenings of the extracts were carried out. It was observed that ethanol extract of V. zizanioides (100, 250, 500 and 750 mg/kg p.w.o) significantly reduced the blood glucose level at the end of 28th days in alloxan-induced diabetes rats. The antihyperglycaemic effects were compared with those of glibenclamide (10 mg/kg p.w.o), the standard reference hypoglycaemic agent. The present study indicates that ethanol extract of V. zizanioides root posses better antihyperglycaemic activity compared to other extracts of it in both normal and alloxan-induced diabetic rats. The study provides proof for the ethnomedical claims and reported biological activities of V. zizanioides with respect to its good therapeutic and antidiabetic potential. We concluded that the ethanolic extract of V. zizanioides has hypoglycaemic and antihyperglycaemic activity as it lowers blood glucose levels in diabetic rats. However, the molecule (s) responsible for such an effect requires further investigation.